2005
DOI: 10.1128/aem.71.3.1394-1404.2005
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Antimicrobial Resistance Observed in Escherichia coli Isolates Obtained from Domestic- and Wild-Animal Fecal Samples, Human Septage, and Surface Water

Abstract: A repeated cross-sectional study was conducted to determine the patterns of antimicrobial resistance in 1,286 Escherichia coli strains isolated from human septage, wildlife, domestic animals, farm environments, and surface water in the Red Cedar watershed in Michigan. Isolation and identification of E. coli were done by using enrichment media, selective media, and biochemical tests. Antimicrobial susceptibility testing by the disk diffusion method was conducted for neomycin, gentamicin, streptomycin, chloramph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

36
206
3
11

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(267 citation statements)
references
References 41 publications
36
206
3
11
Order By: Relevance
“…These results differ from those obtained by other authors such as Sayah et al (2005) or Knezevic and Petrovic (2008) who obtained higher multidrug-resistance for E. coli isolated from pigs than for E. coli isolated from poultry and cattle. Multiresistant strains could have been originated as the result of co-selection of resistance determinants, because exposing a bacterial population to one antimicrobial agent may result in resistance to other agents without any additional exposure (Sayah et al, 2005). Thus, it was reported that higher levels of multiresistant strains in any group may also reflect more recent antibiotic usage (Van den Bogaard et al, 2001).…”
Section: Resultscontrasting
confidence: 57%
See 2 more Smart Citations
“…These results differ from those obtained by other authors such as Sayah et al (2005) or Knezevic and Petrovic (2008) who obtained higher multidrug-resistance for E. coli isolated from pigs than for E. coli isolated from poultry and cattle. Multiresistant strains could have been originated as the result of co-selection of resistance determinants, because exposing a bacterial population to one antimicrobial agent may result in resistance to other agents without any additional exposure (Sayah et al, 2005). Thus, it was reported that higher levels of multiresistant strains in any group may also reflect more recent antibiotic usage (Van den Bogaard et al, 2001).…”
Section: Resultscontrasting
confidence: 57%
“…In this case, it is reasonable to think that ciprofloxacinresistant E. coli could reach vegetable foods though human or poultry farm-influenced wastewater or sewage (Sabate´et al, 2008;Sayah et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…foram os gêneros e espécies bacterianas com maior percentual de resistência a diferentes antimicrobianos, podendo configurar o possível surgimento, no futuro, de cepas multirresistentes. Estudos realizados com intuito de avaliar a resistência de cepas de Escherichia coli oriundas de aves silvestres (Livermore et al 2001, Sayah et al 2005, Dolejska et al 2007, Gibbs et al 2007, demonstraram o ocorrência de cepas multirresistentes. Este dado reveste-se de relevância tendo em vista que, no momento das colheitas, foi observado que outras espécies de pássaros tinham acesso a fezes desses cracídeos possibilitando a veiculação desta bactéria para outros animais, locais, e inclusive, para humanos.…”
Section: Resultsunclassified
“…The usage of antimicrobial agents is considered the most important factor in the selection and dissemination of antimicrobial-resistant bacteria. Although antimicrobial agents are not generally administered to wild animals, the prevalence of antimicrobial-resistant Escherichia coli isolates was determined in some wild animals [4,5,7,10,12,13]. The source of antimicrobial-resistant bacteria among wild animals is still debatable.…”
mentioning
confidence: 99%